PENEGAKAN HUKUM PIDANA TERHADAP IMIGRAN ILLEGAL MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Flora, Henny Saida (Fiat Iustitia : Jurnal Hukum, 2020)
Law Enforcement is essentially the upholding of ideas or concepts as well as an effort to realize the ideas of people's expectations to become reality. Law enforcement against criminal acts of abuse of residence permit in the immigration environment is carried out by the Civil Servant Investigator. In enforcing the law against perpetrators of misuse of residence permits, Civil Servants of immigration can coordinate with domestic law enforcement agencies, namely the Indonesian National Police, prosecutors and judges. The reality in the field often results in problems in the criminal investigation process carried out by the National Police and Civil Servant Investigators (PPNS) always experiencing ups and downs. The ups and downs can take the form of an incomplete investigation or an incomplete investigation such as the completion of a filing. Many cases of abuse of residence permit only go to the stage of administrative action. Enforcement of criminal law against illegal immigrants entering and entering Indonesian territory without going through immigration checks, namely that in resolving cases or law enforcement criminal acts against illegal immigrants entering and entering Indonesian territory are carried out in two ways namely administrative immigration actions (outside the criminal justice system) and actions projustitia (justice process) included in the criminal justice system (Criminal Justice System).